2014
DOI: 10.1111/jocd.12083
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of red orange extract supplementation against UV‐induced skin damages: photoaging and solar lentigines

Abstract: Red orange extract intake can strengthen physiological antioxidant skin defenses, protecting skin from the damaging processes involved in photo-aging and leading to an improvement in skin appearance and pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
(56 reference statements)
0
31
0
8
Order By: Relevance
“…Recently, increasing effort has been devoted to reveal the relationship between food intake and skin condition, which led to the modern concept of "skin care from within" [5,13]. It has been reported that some nutrients, such as vitamin A, E, C, as well as the herbal extracts, such as pycnogenol, orange extract and grape seeds extract exhibited skin lightening effects due to their antioxidant effects [5,6,14]. In this respect, the importance of the dietary source for photoprotection has attracted a great interest.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing effort has been devoted to reveal the relationship between food intake and skin condition, which led to the modern concept of "skin care from within" [5,13]. It has been reported that some nutrients, such as vitamin A, E, C, as well as the herbal extracts, such as pycnogenol, orange extract and grape seeds extract exhibited skin lightening effects due to their antioxidant effects [5,6,14]. In this respect, the importance of the dietary source for photoprotection has attracted a great interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the exposure time is further extended to 15 min, it will lead to skin damage (McKenzie et al 2009). In addition, long-term exposure of skin against UV radiations leads to premature aging or photoaging, which is characterized by wrinkle formation, hyperpigmented lesions or age spots, and decrease in the integrity of the skin (Puglia et al 2014). Photoaging can be characterized by fragmentation and reduced production of collagen in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…자외선 B (ultraviolet B, UVB)는 최근 오존층 파괴로 인한 투과가 증가되는 추세이며 [31], 따라서 UVB에 대한 피부의 노출에 의하여 피부 질환 및 광 노화 등이 증가되고 있다 [19].…”
Section: 서 론unclassified